2005
DOI: 10.1071/ar04241
|View full text |Cite
|
Sign up to set email alerts
|

Induction of embryo development and fixation of partial interspecific lines after pollination of F1 cotton interspecific hybrids (Gossypium barbadense × Gossypium hirsutum) with pollen from Hibiscus cannabinus

Abstract: The possibility of inducing embryo development after pollination of F1 interspecific cotton hybrids (Gossypium barbadense × Gossypium hirsutum) and their reciprocals with pollen from Hibiscus cannabinus was investigated. For this, flowers of F1 plants from 4 G. barbadense × G. hirsutum interspecific hybrids (B403 × Acala Sindos, Carnak × 4S, B403 × Coker 310, and Carnak × Acala Sindos) and their reciprocals grown in the field were pollinated with pollen from Hibiscus cannabinus. From the 443 pollinated flowers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
1
8
0
7
Order By: Relevance
“…However, in the present study, we did not observe any significant differences among genotypes. We chose to use only G. barbadense cultivars as the female parent, because it has been reported that ovules of G. hirsutum 9 G. barbadense cotton hybrids do not react to in vitro culture (Mavromatis et al 2005).…”
Section: Plant Genotypementioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study, we did not observe any significant differences among genotypes. We chose to use only G. barbadense cultivars as the female parent, because it has been reported that ovules of G. hirsutum 9 G. barbadense cotton hybrids do not react to in vitro culture (Mavromatis et al 2005).…”
Section: Plant Genotypementioning
confidence: 99%
“…In cotton haploid production, species within the Malvaceae could be used as potential inducers of gynogenesis. H. cannabinus has been reported to cause in situ parthenogenesis in cotton (Zhou et al 1991;Mavromatis et al 2005). There is a natural incompatibility system that prevents hybridization and introgression with cotton (Kantartzi and Roupakias 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Since all attempts for the creation of pure lines with the use of cotton monosomics (Galanopoulou-Sendouca and Roupakias 1999), haploid production by in-vitro anther and microspore culture (Bajaj and Gill 1996; Goodin and Trolinder 1990;Turaev and Shamina 1986;Mavromatis and Roupakias 1994) or unfertilized ovules (Mavromatis and Roupakias 1995) have been unsuccessful, the only alternative remaining for the production of dihaploids in relatively large numbers was pollination with alien pollen. Accordingly, Mavromatis et al (2005) attempted to pollinate F 1 cotton hybrids (G. barbadense · G. hirsutum) with pollen from Hibiscus cannabinus. This work resulted mixoploid fertile plants in which somatic chromosome numbers ranged from 27 to 42.…”
Section: Discussionmentioning
confidence: 99%
“…The next step is to investigate the possibility of obtaining plants in advanced generations with increased and finally stabilized number of chromosomes at the level of 52, as occurred in crosses of the interspecific hybrid with H. cannabinus (Mavromatis et al 2005). If euploidy is not obtained we will try to exploit the system of alien pollination for the development of aneuploid plants without the use of radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation